2012
DOI: 10.1038/mt.2011.216
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Pleiotrophin Overexpression Provides Functional and Morphological Neuroprotection in the 6-Hydroxydopamine Model

Abstract: Neurotrophic factors are integrally involved in the development of the nigrostriatal system and in combination with gene therapy, possess great therapeutic potential for Parkinson's disease (PD). Pleiotrophin (PTN) is involved in the development, maintenance, and repair of the nigrostriatal dopamine (DA) system. The present study examined the ability of striatal PTN overexpression, delivered via psueudotyped recombinant adeno-associated virus type 2/1 (rAAV2/1), to provide neuroprotection and functional restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 51 publications
2
34
1
Order By: Relevance
“…To evaluate the potential neuroprotective role of PTN against amphetamine-induced neurotoxicity, we have now studied the effects of this drug in the striatum of mice with transgenic overexpression of PTN in the brain. In support of this rationale, studies with parkinsonian toxins had previously shown that overexpression of PTN exerts neuroprotection in mouse models of PD (Gombash et al, 2012;. Unexpectedly, we found that amphetamine-induced loss of striatal TH and DAT contents is increased in PTN-Tg mice, suggesting that dopaminergic denervation caused by amphetamine is facilitated by PTN overexpression.…”
Section: Discussionsupporting
confidence: 57%
“…To evaluate the potential neuroprotective role of PTN against amphetamine-induced neurotoxicity, we have now studied the effects of this drug in the striatum of mice with transgenic overexpression of PTN in the brain. In support of this rationale, studies with parkinsonian toxins had previously shown that overexpression of PTN exerts neuroprotection in mouse models of PD (Gombash et al, 2012;. Unexpectedly, we found that amphetamine-induced loss of striatal TH and DAT contents is increased in PTN-Tg mice, suggesting that dopaminergic denervation caused by amphetamine is facilitated by PTN overexpression.…”
Section: Discussionsupporting
confidence: 57%
“…rAAV2/5-mediated protein expression in young adult rats is not maximal until 1 month after injection (Gombash et al , 2012), and it is possible that the aged brain may require more time to achieve maximal GFP expression. Therefore, we utilized protein immunoblotting to more accurately quantify GFP protein levels at varying time points after rAAV2/5 GFP injection.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of TH immunoreactive (THir) neurons in the SN pars compacta (SNpc) or total number of GFP immunoreactive (GFPir) cells was completed as previously described (Gombash et al , 2012). Briefly, stereology was performed using a Nikon Eclipse 80i microscope (Nikon), StereoInvestigator software (Microbrightfield Bioscience, Williston, VT) and Retiga 4000R camera (Qimaging, Surrey, BC Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 We have previously demonstrated that intrastriatal recombinant AAV delivery to overexpress PTN before 6-hydroxydopamine (6-OHDA) is protective of both nigral neurons and terminals and can be functionally restorative; 16 however, neuroprotection was not complete. PTN transduction patterns following intrastriatal delivery indicated significant expression in the striatonigral direct pathway resulting in robust PTN immunoreactivity within terminals in the SN pars reticulata (SNpr), whereas transduction of SNpc DA neurons following intrastriatal vector injection was limited and only observed in unlesioned rats.…”
Section: Introductionmentioning
confidence: 99%